ERBB4 and Multiple MicroRNAs That Target ERBB4 Participate in Pregnancy-Related Cardiomyopathy. (July 2021) - Feyen, Eline; Ricke-Hoch, Melanie; Van fraeyenhove, Jens; Vermeulen, Zarha; Scherr, Michaela; Dugaucquier, Lindsey; Viereck, Janika; Bruyns, Tine; Thum, Thomas; Segers, Vincent F.M.; Hilfiker-Kleiner, Denise; De Keulenaer, Gilles W.
Abstract : Background: Peripartum cardiomyopathy (PPCM) is a life-threatening disease in women without previously known cardiovascular disease. It is characterized by a sudden onset of heart failure before or after delivery. Previous studies revealed that the generation of a 16-kDa PRL (prolactin) metabolite, the subsequent upregulation of miR-146a, and the downregulation of the target gene Erbb4 is a common driving factor of PPCM. Methods: miRNA profiling was performed in plasma of PPCM patients (n=33) and postpartum-matched healthy CTRLs (controls; n=36). Elevated miRNAs in PPCM plasma, potentially targeting ERBB4 (erythroblastic leukemia viral oncogene homolog 4), were overexpressed in cardiomyocytes using lentiviral vectors. Next, cardiac function, cardiac morphology, and PPCM phenotype were investigated after recurrent pregnancies of HZ (heterozygous) cardiomyocyte-specific Erbb4 mice ( Erbb4 F/+ αMHC-Cre +, n=9) with their age-matched nonpregnant CTRLs (n=9–10). Results: Here, we identify 9 additional highly conserved miRNAs (miR-199a-5p and miR-199a-3p, miR-145a-5p, miR-130a-3p, miR-135a-5p, miR-221-3p, miR-222-3p, miR-23a-3p, and miR19b-3p) that target tyrosine kinase receptor ERBB4 and are over 4-fold upregulated in plasma of PPCM patients at the time of diagnosis. We confirmed that miR-146a, miR-199a-5p, miR-221-3p, miR-222-3p, miR-23a-3p, miR-130a-5p, and miR-135-3p overexpression decreases ERBB4 expression in cardiomyocytes (−29% to −50%; P <0.05). In addition, we demonstrate that genetic cardiomyocyte-specific downregulation of Erbb4 during pregnancy suffices to induce a variant of PPCM in mice, characterized by left ventricular dilatation (postpartum second delivery: left ventricular internal diameter in diastole, +19±7% versus HZ-CTRL; P <0.05), increased atrial natriuretic peptide (ANP) levels (4-fold increase versus HZ-CTRL mice, P <0.001), decreased VEGF (vascular endothelial growth factor) and VE-cadherin levels (−33±17%, P =0.07; −27±20%, P <0.05 versus HZ-CTRL), and histologically enlarged cardiomyocytes (+20±21%, versus HZ-CTRL, P <0.05) but without signs of myocardial apoptosis and inflammation. Conclusions: ERBB4 is essential to protect the maternal heart from peripartum stress. Downregulation of ERBB4 in cardiomyocytes induced by multiple miRNAs in the peripartum period may be crucial in PPCM pathophysiology. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT00998556. Abstract : Supplemental Digital Content is available in the text.